Influence of eye movements, auditory perception, and phonemic awareness in the reading process. Issue 6 (1st November 2016) - Megino-Elvira, Laura; Martín-Lobo, Pilar; Vergara-Moragues, Esperanza
ABSTRACT: The authors' aim was to analyze the relationship of eye movements, auditory perception, and phonemic awareness with the reading process. The instruments used were the King-Devick Test (saccade eye movements), the PAF test (auditory perception), the PFC (phonemic awareness), the PROLEC-R (lexical process), the Canals reading speed test, and the ACL-1 (reading comprehension). The sample was composed of 52 first-year primary school pupils. After the correlational analysis, results indicate that all of these factors correlate in reading (lexical process, speed, and word comprehension). Moreover, the nonparametric Mann-Whitney U test reveals that children with saccade eye movements and auditory perception problems obtain lower reading levels. In addition, children with lexical problems obtain a lower level of phonemic awareness. Given the importance of these variables, the authors conclude with a proposal of neuropsychological activities to improve reading skills.